Light flashes during proton and photon radiotherapy: A multicenter prospective observational study - Masashi Mizumoto (Elsevier, 2021)
Background: Patients who receive radiation therapy sometimes complain of a light flash during irradiation. The details of the characteristics of this light have not been described. Purpose: To evaluate light flashes during photon and proton radiotherapy. Methods and Materials: A prospective observational study was performed in all adult patients (≥20 years old) who received photon and proton therapy at two centers between January 2019 and August 2020, except for patients who could not communicate and those with visual abnormality. Evaluations were obtained for the presence or absence of light flashes, light darkness (7 levels), light intensity (5 levels), frequency, light movement, light flashing, and time seeing the light, using a weekly checklist. Results: A total of 650 courses were examined for 621 patients, of whom 416 received photon radiotherapy and 205 received proton beam therapy. The checklist indicated that 88 patients (16.1%) sensed light during photon or proton radiotherapy. In multivariate logistic regression analysis, the factors that were significantly associated with a light flash were a higher retina dose and younger age (p < 0.001). Light flashes were seen by only 35/524 patients (6.7%) for whom the retina was not irradiated, but by 13/33 (39.4%) and 41/64 (64.1%) with maximum isodose lines for the retina of 10–50% and 60–100%, respectively. The numbers of patients who sensed blue, purple, yellow, red, white and other colors were 52, 15, 15, 9, 16 and 8, respectively (multiple selections possible). Light movement was observed by 52 patients (59%). The location of the light was defined as near, far, and middle by 70, 13, and 5 patients, respectively. The median time the light was seen was 10 s. Conclusions: Many patients sense light flashes during radiotherapy. The retina dose and a younger age were significantly associated with the frequency of light flashes.